Morphology and multi-gene phylogeny reveal Pestalotiopsis pinicola sp. Nov. and a new host record of cladosporium anthropophilum from edible pine (Pinus armandii) seeds in Yunnan Province, China - Saowaluck Tibpromma (2020)
© 2019 by the authors. Licensee MDPI, Basel, Switzerland. This study contributes new knowledge on the diversity of conidial fungi in edible pine (Pinus armandii) seeds found in Yunnan Province, China and emphasizes the importance of edible seed products to ensure food safety standards. We isolated two fungal species, one on the pine seed coat and the other on the endosperm of the pine seed. The two fungal species were identified as Pestalotiopsis pinicola sp. nov. and a new host record Cladosporium anthropophilum. Characteristic morphological features of Pestalotiopsis pinicola were used alongside results from multi-gene phylogenetic analysis to distinguish it from currently known species within the genus. Cladosporium anthropophilum was identified as a new host record based on morphological features and phylogenetic analysis. In addition, detailed descriptions, scanned electron microscopy morphology, illustrations, and phylogenetic trees are provided to show the placement of these species.